Дослідження та програмна реалізація системи Software Defined Storage - Молчанов, Юрій Володимирович; Molchanov, Yurii (ЦНТУ, 2025)
В даній випускній кваліфікаційній роботі за другим (магістерським) рівнем вищої освіти розроблено програмне забезпечення, яке призначено для системи Software Defined Storage. Метою розробки є дослідження та програмна реалізація системи Software Defined Storage. Об’єктом дослідження є процес Software Defined Storage. Предметом дослідження є методи Software Defined Storage. In this final qualification work for the second (master's) level of higher education, software designed for the Software Defined Storage system has been developed. The purpose of the development is the research and software implementation of the Software Defined Storage system. The object of the research is the Software Defined Storage process. The subject of the research is the Software Defined Storage methods.
Research and software implementation of the Software Defined Storage system
Keywords: комп’ютерна інженерія; Software Defined Storage; computer engineering